Moving toward Net Zero Carbon Buildings to Face Global Warming: A Narrative Review - Davide Tirelli; Daniela Besana (Buildings, 2023)
The increase in global surface temperatures will surpass the 2 °C target set by the Paris Agreement unless carbon emissions are lowered to zero by 2050. To date, the building sector is responsible for 38% of all carbon emissions, thus one of the main targets is represented by the development of building strategies that can facilitate the transition toward carbon-neutral buildings. The main strategies are today represented by nearly zero energy buildings (nZEBs), zero energy buildings (ZEBs)/net zero energy buildings (NZEBs) and net zero carbon buildings (NZCBs). Particularly, NZCBs completely target zero operational and embodied carbon during their life cycles, fulfilling the leadership role in the decarbonization of the construction sector. Moreover, adopting the European Standard EN 15978:2011, carbon emissions can be precisely classified to enhance strategies aimed at reducing them. Commercial viability remains a fundamental economic driver, but the higher initial capital costs hinder the NZCBs. In addition, legislative, socio-cultural, technological, professional and geographical barriers hold back its diffusion. NZCBs can be met by a four-steps program: embodied carbon reduction, operational carbon reduction, increase in renewable energy supply and offset and carbon storage. Circular economy principles are strictly connected to design for disassembly and for adaptability to reduce embodied carbon, while passive design and solar and geothermal energy production can satisfy the renewable energy demand of the building. The aim of this narrative review is to determine and describe which is the current state of the art for NZCB definition, the drivers and barriers toward its application in a broader context and which strategies are eligible to meet the ambitious goal of zero operational and zero embodied carbon emissions.